Taxonomic review of the genus Lemyra Walker (Erebidae: Arctiinae) from India - Singh, Harsimranjeet; Raha, Angshuman; Kirti, Jagbir Singh; Singh, Navneet (Zootaxa, 2024)
In the present manuscript, we review the genus Lemyra Walker, 1856 from India by examining the specimens collected freshly from different parts of India from 2016 to 2019 and from the National Zoological Collection of the Zoological Survey of India (NZCZSI). The revised status of Lemyra in India is presented by describing seven new species: Lemyra (Thyrgorina) rubripecta sp. nov., L. (T.) densimacula sp. nov., L. (T.) fortiorspina sp. nov., L. (T.) apatani sp. nov., L. (T.) adunca sp. nov., L. (T.) obsoleta sp. nov. and L. (T.) pinus sp. nov., synonymizing equal number of species: L. (T.) punctilinea (Moore, 1879), syn. nov. under L. (T.) flavalis (Moore, 1865), L. (T.) magnaproteus N. Singh & Kirti, 2016, syn. nov. under L. (T.) proteus (De Joannis, 1928), Thanatarctia costalis Kaleka, 2012: 51, syn. nov., Thanatarctia collarlis Kaleka, 2012: 53, syn. nov., L. (T.) collarlis N. Singh, Kirti & Kaleka, 2016: 15, syn. nov. (objective synonym of T. collarlis Kaleka, 2012), L. (T.) pseudocollarlis N. Singh, Kirti & Kaleka, 2016: 16, syn. nov. under L. (T.) nigrescens (Rothschild, 1910) and L. (T.) angularis (Strand, 1919) under L. (T.) spilosomata (Walker, [1865]). The status of L. (T.) aurantiaca (Fang, 1985), a new record to India, is upgraded to species level. Additionally, two species i.e., L. (T.) kaikarisi Saldaitis et al., 2019 and L. (T.) persephone Saldaitis et al., 2020 are reported for the first time from India. An updated checklist of 117 species (including the nominotypical subspecies) and 10 subspecies of Lemyra is provided with 48 species (including the new records and new species described herein) from India. Of the 48 species from India, the systematics of 42 species is provided based on their voucher specimens. We could not study the rest of the six species with their voucher specimens. The detailed diagnoses with closely similar congeners, genitalia illustrations, distributions, individual variations and sexual dimorphism, if any, and bionomics is provided.